Coherent population trapping magnetometer by differential detecting magneto–optic rotation effect - 张樊 田原 张奕 顾思洪 (Chinese physics B, 2016)
A pocket coherent population trapping（CPT） atomic magnetometer scheme that uses a vertical cavity surface emitting laser as a light source is proposed and experimentally investigated.Using the differential detecting magneto–optic rotation effect,a CPT spectrum with the background canceled and a high signal-to-noise ratio is obtained.The experimental results reveal that the sensitivity of the proposed scheme can be improved by half an order,and the ability to detect weak magnetic fields is extended one-fold.Therefore,the proposed scheme is suited to realize a pocket-size CPT magnetometer.